2018
DOI: 10.1177/1557988318776581
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prioritization and Risk Perception Among an Online Sample of Men Who Have Sex With Men in the United States

Abstract: Men who have sex with men (MSM) may prioritize interpersonal and structural factors, such as LGBTQ-related inequalities, housing instability, financial insecurity, and relationship seeking, over HIV prevention. The aim of this study was to assess how MSM prioritize HIV relative to other factors and the association between HIV prioritization, HIV testing and sexual risk behavior, and perceived risk. Data were collected from a national online survey of MSM in the United States assessing HIV knowledge and priorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
(56 reference statements)
4
17
0
1
Order By: Relevance
“…MSM reporting high-risk behavior measured by the HIRI-MSM, condomless receptive anal sex and increased number of partners were more likely to perceive themselves at higher risk, which is consistent with a web-based study conducted among 800 MSM from the United States [21]. However, we also found that a high proportion of MSM reporting high-risk behavior do not perceive themselves at high-risk for HIV (~60%).…”
Section: Discussionsupporting
confidence: 89%
“…MSM reporting high-risk behavior measured by the HIRI-MSM, condomless receptive anal sex and increased number of partners were more likely to perceive themselves at higher risk, which is consistent with a web-based study conducted among 800 MSM from the United States [21]. However, we also found that a high proportion of MSM reporting high-risk behavior do not perceive themselves at high-risk for HIV (~60%).…”
Section: Discussionsupporting
confidence: 89%
“…MSM reporting high-risk behavior measured by the HIRI-MSM, condomless receptive anal sex and number of partners were more likely to perceive themselves at higher risk, which is consistent with a web-based study conducted among 800 MSM from the United States (21). However, we also found that a high proportion of MSM reporting high-risk behavior do not perceive themselves at high-risk for HIV (~60%).…”
Section: Discussionsupporting
confidence: 89%
“…MSM reporting high-risk behavior measured by the HIRI-MSM, condomless receptive anal sex and number of partners were more likely to perceive themselves at higher risk, which is consistent with a web-based study conducted among 800 MSM from the United States (22). However, we also found that a high proportion of MSM reporting high-risk behavior do not perceive themselves at high-risk for HIV (~60%).…”
Section: Discussionsupporting
confidence: 89%